The Role of European Union (EU) regional energy policy in enhancing energy security and its implications for the Asian region - SUH, Yun Ji (KDI School, 2017)
Historically, energy policy has been a national issue as it is closely related to national security and sovereignty. However, since the oil shock in the early 1970s, it has become a transnational issue that requires collective efforts to tackle any vulnerability that could happen to energy importers. This paper identifies the benefits of regionally integrated energy policy with regards to enhancing energy security. It is based on the EU's experience, thew orld's largest energy importer. By showing energy security index that reflects seven factors from the dimension of availability and adaptability of energy system, I conclude that regional energy policy largely helps to improve EU's energy security level by advancing its inter-border infrastructure capacity, market integrity and sharing common standards and regulations. In light of these findings, I propose that the Asia region could consider the practices followed in the EU in formulating regional energy policy that include energy efficiency standards, which does not require immediate physical infrastructure connection or large amount of capital investment. Due to the given limitation of governance structure and geographical barriers, it seems appropriate
Thesis(Master) --KDI School:Master of Development Policy,2017